2016
DOI: 10.1186/s13014-016-0688-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeated iodine-125 seed implantations combined with external beam radiotherapy for the treatment of locally recurrent or metastatic stage III/IV non-small cell lung cancer: a retrospective study

Abstract: BackgroundRecurrent or metastatic lung cancer is difficult to manage. This retrospective study aimed to assess the efficacy of repeated iodine-125 seed implantations combined with external beam radiotherapy (EBRT) for locally recurrent or metastatic stage-III/IV non-small cell lung cancer (NSCLC).MethodsEighteen previously treated stage-III/IV NSCLC patients with local or metastatic recurrences underwent 1-to-3 iodine-125 implantations. Six of these patients received palliative EBRT and six patients received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…1A and 2C) and the rest were treated with freehand implantation. The median number of seeds implanted was 57 (range, 14-100) and the median number of needles was 5 (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Postoperative dosimetric measurements demonstrated that the actual D90 ranged between 79 and 148 Gy (mean D90, 113 Gy; Table SI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A and 2C) and the rest were treated with freehand implantation. The median number of seeds implanted was 57 (range, 14-100) and the median number of needles was 5 (range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Postoperative dosimetric measurements demonstrated that the actual D90 ranged between 79 and 148 Gy (mean D90, 113 Gy; Table SI).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that iodine-125 ( 125 I) seed implantation brachytherapy exhibits good clinical results as a minimally invasive and effective treatment for a variety of tumors, such as pancreatic or liver cancer and gynecologic malignancies (6)(7)(8). Recently, 125 I brachytherapy has been used for the treatment of lung cancers; however, most of these studies focused on assessing the effectiveness of 125 I brachytherapy combined with chemotherapy or radiotherapy (3,5,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is difficult to deliver a sufficient radiation dose to tumors using external beam radiotherapy alone because of the obstruction of surrounding tissues (12). Radioactive seed implantation has been reported to be successfully applied for treating inoperable solitary lung cancers, while avoiding excessive radiative exposure to surrounding normal tissues (13), such as iodine-125 ( 125 I) seed implantation. However, there still remains illusiveness whether 125 I radiation can improve the resistance of NSCLC to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the incidence of severe irradiation-related adverse effects is signi cantly reduced and the slight complications could disappear soon with supportive care (8). Because of the mentioned advantages, patients including the elderly, have showed great interest and good compliance (14)(15)(16)(17).…”
mentioning
confidence: 99%